2008
DOI: 10.1007/s11661-008-9684-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Creep Crack Growth Behavior of a Near-α Titanium Alloy IMI-834

Abstract: In the present study, the effect of microstructure (i.e., a + b and transformed b) on creep crack growth (CCG) behavior of a near-alpha (IMI 834) titanium alloy has been explored at temperatures 550°C and 600°C. For characterizing the CCG behavior of the alloy, both stress intensity factor (K) and energy integral parameter (C t ) were used in the present investigation. The use of stress intensity factor (K) as crack-tip parameter is not appropriate in the present study as no unique correlation between crack gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…A recent study 4 has revealed that a path independent energy line integral parameter like C* or C t is a more appropriate crack tip parameter than the stress intensity parameter K for characterising CCG behaviour in Timetal 834 Ti alloy. This is because the stress intensity parameter K could not uniquely describe the crack growth rate data over the entire range, as it does not take transient effects in crack growth rate into account.…”
Section: Creep Crack Growth Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study 4 has revealed that a path independent energy line integral parameter like C* or C t is a more appropriate crack tip parameter than the stress intensity parameter K for characterising CCG behaviour in Timetal 834 Ti alloy. This is because the stress intensity parameter K could not uniquely describe the crack growth rate data over the entire range, as it does not take transient effects in crack growth rate into account.…”
Section: Creep Crack Growth Behaviourmentioning
confidence: 99%
“…Several investigators13 have reported that the Ti alloys with fully transformed β structure exhibit superior creep and stress rupture properties as compared to bimodal microstructure consisting of primary α and transformed β . Furthermore, a recent study by the authors4 has revealed that the Timetal 834 alloy with fully transformed β structure also exhibits better creep crack growth (CCG) resistance. However, Ti alloys with fully transformed β structure is well known to exhibit inferior fatigue properties 2,5 – 7.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed fractographic and microstructural examination of damage zone has revealed that the creep crack growth in stable crack growth regime comprises two stages viz., (i) nucleation of microvoids / microcracks around crack tip and (ii) growth and coalescence of microvoids / microcracks, which subsequently joins the main crack. Microcracks have been found to form, by fracture of primary α particles at the specimen surface in bimodal microstructure (Fig.4b) [4]. This may be due to the well documented fact that α phase has got more affinity as well as solid solubility for oxygen.…”
Section: Resultsmentioning
confidence: 89%
“…A recent study [4] has revealed that a path independent energy line integral parameter like C* or C t is more appropriate crack tip parameter than the stress intensity parameter, K, for characterizing creep crack growth behaviour in IMI 834 titanium alloy. This is because the stress intensity parameter, K, could not uniquely describe the crack growth rate data over entire range as it does not take transient effects in crack growth rate into account.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation